2020
DOI: 10.1001/jamanetworkopen.2020.13802
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression With Past-Month Cannabis Use Among US Adults Aged 20 to 59 Years, 2005 to 2016

Abstract: IMPORTANCE Despite studies showing that repeated cannabis use may worsen depressive symptoms, the popular media increasingly presents cannabis as beneficial to mental health, and many members of the public view cannabis as beneficial for depression. Therefore, cannabis use among individuals with depression may be becoming more prevalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 39 publications
10
38
1
Order By: Relevance
“…Our results, along with those from a recent study, 48 suggest that adults with MDE may be particularly vulnerable to cannabis use as beliefs in its therapeutic potential become more widespread and products become more accessible. Moreover, even after adjusting for depression, 55,56 our results underscore an urgent need for prevention interventions designed specifically for young people before first cannabis exposure and highlight the importance of early screening for daily cannabis use and CUD as well as CUD treatment, especially among young women.…”
Section: Discussionsupporting
confidence: 75%
“…Our results, along with those from a recent study, 48 suggest that adults with MDE may be particularly vulnerable to cannabis use as beliefs in its therapeutic potential become more widespread and products become more accessible. Moreover, even after adjusting for depression, 55,56 our results underscore an urgent need for prevention interventions designed specifically for young people before first cannabis exposure and highlight the importance of early screening for daily cannabis use and CUD as well as CUD treatment, especially among young women.…”
Section: Discussionsupporting
confidence: 75%
“…While there is no consensus on the definition of heavy cannabis use, this threshold was used to remain consistent with previous studies. 13 , 20 …”
Section: Methodsmentioning
confidence: 99%
“… 10 12 A recent study using the U.S.-based, nationally representative data set from the National Health and Nutrition Examination Survey (NHANES) found that adults with depression had greater odds of cannabis use in the past month compared to those without depression. 13 Individuals with depression who also use cannabis are postulated to be at higher risk for further adverse mental health outcomes. 14 There are concerns about increased suicidal ideation or suicide attempts with acute or chronic cannabis use, though there is insufficient evidence to claim causality.…”
Section: Introductionmentioning
confidence: 99%
“…However, such studies demonstrating correlation have yet to confirm causation, which should be determined by a model’s ability to predict. (Arrow, 1963) Although those reporting depression to SAMHSA have increasingly used marijuana since states began increasing access to regulated cannabis, (Gorfinkel, Stohl, & Hasin, 2020) we observe no evidence that these laws have predictive relationships with reports of any mental illness. Additionally, recreational marijuana access is followed by reductions in suicide for some age groups.…”
Section: Public Health Implications and Conclusionmentioning
confidence: 71%
“…(Delforterie, et al, 2015) In a 2020 study in JAMA Network Open , Gorfinkel et al found that people reporting depression tend to use marijuana at a higher rate. (Gorfinkel, Stohl, & Hasin, 2020)…”
mentioning
confidence: 99%